2017
DOI: 10.1038/s41598-017-06096-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure to arsenic causes hearing loss in young people aged 12–29 years and in young mice

Abstract: There is no information on the association between oral exposure to arsenic (As) and hearing loss in humans or mice. In this combined epidemiological study and experimental study, the association of oral exposure to As with hearing loss in people aged 12–29 years and young mice was examined. Subjects in the exposure group (n = 48), who were drinking tube well water contaminated with As, showed significantly higher risks of hearing loss at 4 kHz [odds ratio (OR) = 7.60; 95% confidence interval (CI): 1.56, 57.88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Neither randomization nor blinding investigation were used in this animal study. In brief, we exposed mice (n = 7) to 22.5 mg/L of sodium arsenite (NaAsO 2 , Sigma-Aldrich) dissolved in distilled water for 2 months via drinking water and changed the drinking water every week as previously described [ 16 ]. The exposure dose was based on the As exposure for mice at 10 and 100 ppm via drinking water in a previous study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither randomization nor blinding investigation were used in this animal study. In brief, we exposed mice (n = 7) to 22.5 mg/L of sodium arsenite (NaAsO 2 , Sigma-Aldrich) dissolved in distilled water for 2 months via drinking water and changed the drinking water every week as previously described [ 16 ]. The exposure dose was based on the As exposure for mice at 10 and 100 ppm via drinking water in a previous study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study using pure tone audiometry (PTA), an association of oral exposure to As via drinking water with hearing loss in young people was shown by multivariate analysis with adjustments for confounders including age, smoking, sex and BMI [ 16 ]. However, multivariate analysis has not been performed to demonstrate the association of As levels in nails with hearing loss in humans, although age and smoking are known to be strong factors affecting hearing levels in humans [ 14 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Oxidative stress status is an imbalance between the production of active oxygen species and the ability of a biological system to eliminate these compounds, which results in damage to the biological system and consequently organ dysfunction. 8,9 Oxidative stress is one of the ways of the main causes of renal failure. 10 It has been shown that an increase in free radical production causes loss of function in the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…In our participants, contaminated drinking water was less of a problem than direct exposure of the ears, eyes, mouth, or nose to air containing high concentrations of arsenic. Furthermore, previous studies revealed that chronic arsenic exposure caused eye diseases (See et al 2007 ; Sinczuk-Walczak et al 2010 ; Chen 2014 ), hearing impairment (Kesici et al 2016 ; Li et al 2017 ), oral cavity lesions (Sarwar et al 2010 ; Syed et al 2013 ), olfactory dysfunction (Ishinishi et al 1977 ; Mukherjee et al 2014 ), and memory impairment (Tyler and Allan 2014 ). Arsenic levels in some of our participants’ hair were found to be high when the Toroku Medical Examination was first administered (10 years after exposure ended).…”
Section: Discussionmentioning
confidence: 99%